(untitled) (Journal of Dhaka National Medical College & Hospital, 2018)
Background: The complications, therapy and prognosis are significantly determined by the extent of coronary artery involvement in unstable angina. Although the 12- lead electrocardiogram (ECG) has been found useful in identifying different coronary arteries involvement in unstable angina, it has traditionally been felt to be incapable of localizing the culprit lesion of different coronary arteries. Such a capability would be important, because unstable angina due to multivessel involvement carry a worse prognosis than those with single vessel lesion. Objective: The aim of the present study was to find out the ECG changes and extent of coronary artery involvement in patients of unstable angina, then correlate and compare the ECG changes with angiographic findings among these patients group. Methods: This cross sectional analytical study was conducted from August, 2016 to January, 2017 in the Department of Cardiology, Dhaka National Medical College & Hospital. Patients admitted with chest pain and diagnosed as unstable angina were selected for the study. A total of 70 patients were enrolled in this study. Among them 2 patients died in hospital due to complications of unstable angina and 6 patients did not agree to do coronary angiogram. Later on, 62 patients who got conventional standard management and subsequently underwent coronary angiography within 15 days of index event were included in the study. Based on the presence of significant ST-segment depression or T wave inversion, the study subjects were divided in to two groups. In group A (n=31), patients with ST-segment depression in at least two consecutive leads. In group B (n=31), patients with T wave inversion in at least two consecutive leads. These different patterns of ECG changes in unstable angina were correlated with angiographic findings and number of coronary arteries involved. Results: In this study, mean age was (53.3+12.5 in group A Vs 51.5±10.3 years in group B. Male to female ratio of the whole study population was 2.6:1. Left ventricular ejection fraction (LVEF) was in group A and group B(48.35±5.37% Vs 56.7±6.86%). Regarding the extent of coronary artery involvement. In group A, the presence of SVD was 6.5%,DVD was48.4%,TVD was 38.7% and Normal/Non critical coronary artery disease 6.5%. On the other hand in group B, 45.2%, 6.5%, 0.0% and 48.4% cases respectively. So significantly more patients had extensive coronary artery involvement in patients of having ST segment depression (group A) than patients having T wave inversion (group-B). [P=0.001]. Conclusion: This study showed that significant ST segment depression rather than T wave inversion has better correlation with more extensive coronary artery involvement in patients of unstable angina. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 14-18